2021
DOI: 10.1017/s0033291721001860
|View full text |Cite
|
Sign up to set email alerts
|

Improving perinatal sleep via a scalable cognitive behavioural intervention: findings from a randomised controlled trial from pregnancy to 2 years postpartum

Abstract: Background Sleep disturbance is common in gestational parents during pregnancy and postpartum periods. This study evaluated the feasibility and efficacy of a scalable cognitive behavioural therapy (CBT) sleep intervention tailored for these periods. Methods This is a two-arm, parallel-group, single-blind, superiority randomised controlled trial. Nulliparous females without severe medical/psychiatric conditions were randomised 1:1 to CBT or attention- and time-matched control. All partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…33 Treating insomnia in pregnancy also appears to reduce symptoms of depression, with evidence showing benefit up to 2 years postpartum. 30 , 32 Data from this study, and others longitudinal cohorts add to a burgeoning literature showing the impact of untreated sleep problems on later symptoms of depression, and point to an urgent need for accessible treatment options to be disseminated. 4 , 5 , 34 …”
Section: Discussionmentioning
confidence: 64%
“…33 Treating insomnia in pregnancy also appears to reduce symptoms of depression, with evidence showing benefit up to 2 years postpartum. 30 , 32 Data from this study, and others longitudinal cohorts add to a burgeoning literature showing the impact of untreated sleep problems on later symptoms of depression, and point to an urgent need for accessible treatment options to be disseminated. 4 , 5 , 34 …”
Section: Discussionmentioning
confidence: 64%
“…Those that did collect follow up data show mixed findings (long term improvement in five studies, short term but no long-term improvement in six studies, no short term or long-term improvement in eight studies, and no short-term improvement but long-term change in two studies). A recently published study found that CBTi delivered in a community sample over multiple time points during pregnancy and postpartum was associated with improved insomnia severity and sleep disturbance in late pregnancy and at 24 months postpartum, but not at 12 months postpartum [ 88 ], suggesting that within the immediate postpartum timeframe making measurable changes to sleep may be difficult to achieve but that there are long term benefits to supporting sleep at this time.…”
Section: Discussionmentioning
confidence: 99%
“…However, given positive associations between women’s exposure to discrimination and poorer sleep quality in pregnancy, future researchers may also consider examining objective measures of women’s sleep health during pregnancy as potential mediator variables. Our measure of prenatal sleep quality has not been validated among pregnant women despite being used in several studies of perinatal health [ 43 , 66 ]. The use of objective prenatal sleep data may be needed to more fully assess this potential mediator.…”
Section: Discussionmentioning
confidence: 99%